Fedora Linux - Tyler, Chris (O'Reilly, 2006)
"Neither a "Starting Linux" book nor a dry reference manual, this book has a lot to offer to those coming to Fedora from other operating systems or distros."--Behdad Esfahbod, Fedora developerThis book will get you up to speed quickly on Fedora Linux, a securely-designed Linux distribution that includes a massive selection of free software packages. Fedora is hardened out-of-the-box, it's easy to install, and extensively customizable - and this book shows you how to make Fedora work for you. Fedora Linux: A Complete Guide to Red Hat's Community Distribution will take you deep into essential Fe